Enhancing 5G Network Efficiency Using Adaptive Modulation and Coding Schemes - Prasad, Koushik V; Patil, Shashikant; Dadhich, Atul (2024 International Conference on Advances in Computing Research on Science Engineering and Technology (ACROSET), 2024)
This approach incorporates flexibility, intelligence, and efficiency in an attempt to meet the difficulties of today's ever-changing network landscape. The essay begins by highlighting the need of improving 5G network speed to keep up with the expanding needs of our more interconnected society. The suggested approach, which makes use of adaptive modulation and coding schemes, is introduced and set up for investigation in the following sections. These adaptable settings accommodate the various demands of 5G applications while maintaining optimum data rates and network stability in all circumstances. This study's findings show that the suggested technique is superior to the status quo across a variety of important parameters for assessment. Consistently greater throughput, such as 180 Mbps, is achieved using the suggested technique compared to the standard approach, which reaches 150 Mbps. The 15-ms delay it displays is likewise much lower than the 20-ms lag seen with more conventional approaches. In comparison to conventional techniques, which achieve a BER of 0.005 and a packet loss rate of 2 %, the suggested approach achieves a BER of 0.002 and a packet loss rate of 1 %. When compared to conventional approaches, the suggested solution significantly improves network dependability, reaching 95% reliability. The suggested approach has a remarkable spectral efficiency of 4.2 bps/Hz, which is much higher than the efficiency of conventional methods (3.6 bps/Hz). To sum up, the suggested approach to improving 5G network efficiency using adaptive modulation and coding schemes is a shining example of cutting-edge research in the field of telecommunications. The flexibility, intelligence, and efficacy it offers make it an attractive option for the ever-changing 5G landscape. The consequences extend well beyond the technological accomplishments and touch upon healthcare, transportation, entertainment, and the Internet of Things.